PENGARUH PERAN KOMITE AUDIT, PENGENDALIAN INTERNAL, AUDIT INTERNAL DAN PELAKSANAAN TATA KELOLA PERUSAHAAN TERHADAP PENCEGAHAN KECURANGAN - Gusnardi Gusnardi (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2011)
The needs for good corporate governance in the last ten years have been evidenced, especially after the failure of some big companies. In Indonesia, the good corporate governance become more important since this country experienced a multi dimension crisis at the middle of the 1997, where all government agents and private enterprises were required to implement the corporate governance. The purpose of this research is to explore the influence of audit committee role, internal control, internal audit, and good corporate governance implementation simultaneously and partly on the fraud prevention over the state-owned companies. This research was conducted by census methods over 13 public BUMN in Indonesia. The data used in this research were primary data collected by questioners. The research respondents were audit committee chairman, financial director, internal audit department chairman, and corporate secretary. The validity and reliability of the data was tested before hypothesis testing. The data analysis for hypothesis testing was the path analysis. This research concludes the of audit committee role, internal control, internal audit, and good corporate governance implementation influential significant to Fraud prevention the state-owned companies in Indonesia. From this research expressed that optimal from audit committee role, internal control exercise, internal audit and good corporate governance implementation can prevent the happening of fraud prevention over the state-owned companies in Indonesia.